Prescribing decision making by medical residents on night shifts: A qualitative study. Issue 10 (6th June 2022) - Lauffenburger, Julie C.; Coll, Maxwell D.; Kim, Erin; Robertson, Ted; Oran, Rebecca; Haff, Nancy; Hanken, Kaitlin; Avorn, Jerry; Choudhry, Niteesh K.
Abstract: Introduction: Prescribing of medications with well‐known adverse effects, like antipsychotics or benzodiazepines, during hospitalisation is extremely common despite guideline recommendations against their use. Barriers to optimal prescribing, including perceived pressure from allied health professionals and fatigue, may be particularly pronounced for less experienced medical residents, especially during night shifts when these medications are often prescribed. Under these circumstances, physicians may be more likely to use 'quick', often referred to as System 1 choices, rather than 'considered' System 2 strategies for decisions. Understanding how medical residents use, these different cognitive approaches could help develop interventions to improve prescribing. Methods: To understand decision‐making and contextual contributors that influence suboptimal prescribing during night coverage by medical residents, we conducted semi‐structured qualitative interviews with residents in general medicine inpatient settings. The interviews elicited perspectives on shift routines, stressful situations, factors influencing prescribing decision making and hypothetical measures that could improve prescribing. Interviews were audio‐recorded and transcribed. Data were analysed using codes developed by the team to generate themes using immersion/crystallisation approaches. Results: We conducted interviews with 21 medical residents; 47% were female, 43% were White, and 43% were Asian. We identified five key themes: (i) time pressures affecting prescribing decisions, (ii) fears of judgement by senior physicians and peers and being responsible for patient outcomes, (iii) perceived pressure from nursing staff, amplified by nurses' greater experience, (iv) clinical acuity as a key factor influencing prescribing, and (v) strategies to improve communication between members of the care team, like ensuring adequate hand‐off by day teams. Conclusion: Medical residents highlighted numerous contextual factors that promote quick thinking rather than slower thinking when prescribing on night shifts, particularly time constraints, perceived pressure and patient clinical acuity. Interventions aimed at reducing prescribing should address how to manage stress and perceived pressure in decision making. Abstract : Medical residents often rely on mental shortcuts when prescribing medications. Interventions are offered for reducing sub‐optimal prescribing by managing stress and perceived pressure.